Conditions for Exercise by Foreign Citizens of Some Fundamental Social Rights as Subjective Rights - A. I. Petrova (Теоретическая и прикладная юриспруденция)
With a high migration attractiveness of Russia, the issue of the exercise of fundamental social rights by foreigners, including minors, in Russiа is important. The author reviewed the existing regulations, enshrining the right to health and medical care, education, housing and social security, and the practice of the Ombudsman for children in Saint Petersburg. The ways of solving the identified problems in practice and eliminating conflicts in the legislation of Saint Petersburg are proposed.